[RETRACTED ARTICLE] A Study of Factors of Human Resource Management Influencing the Performance of Thai Infrastructure Contractors Using Structural Equation Modeling - Kawapapong, Chanatip; Kokkaew, Nakhon (Engineering and Technology Horizons, 2021)
This article has been retracted by the editorial team of Engineering and Technology Horizons (formerly known as the Ladkrabang Engineering Journal). After an editorial assessment, it was determined that its content significantly overlaps with an article published in another journal. In accordance with the journal's ethical policies and the Committee on Publication Ethics (COPE) Guidelines, the article has been formally retracted. Please note that this administrative action is based entirely on factual findings of content duplication to maintain academic standards and does not constitute a conclusion regarding the intent or liability of any party involved.